Nanoscale X-Ray Diffraction of Silk Fibers - Riekel, Christian; Burghammer, Manfred; Rosenthal, Martin (Frontiers in Materials, 2019)
This report focuses on current possibilities and perspectives of scanning X-ray nanodiffraction for probing nanoscale heterogeneities in silk fibers such as nanofibrillar skin-core morphologies, nanocrystalline inclusions and fine fibers down to submicron diameters.